Transition versus physical climate risk pricing in European financial markets: A text-based approach - Giovanna Bua; Daniel Kapp; Federico Ramella; Lavinia Rognone (European Central Bank (ECB), 2022)
We examine the existence of physical and transition climate risk premia in euro area equity markets. To do so, we develop two novel physical and transition risk indicators, based on text analysis, which are then used to gauge the presence of climate risk premia. Results suggest that climate risk premia for both, transition and physical climate risk, have increased since the time of the Paris Agreement. In addition, we investigate which metrics may be used by investors to proxy a firm's exposure to either physical or transition risk. To this end, we construct portfolios according to the most common firm-specific climate metrics and estimate the sensitivity of these portfolios to our risk indicators. We compare results from these firmlevel proxies to much simpler sectoral classifications to see if investors may simply pigeonhole firms into the industry they operate in. We find that firm level information appears to be used as a gauge for transition risk, in particular since 2015, whereas sectoral classifications appear insufficient. However, sectoral classification may be employed to broadly gauge firms' exposures to physical risk.
Keywords: C58; G12; G14; G28; Q51; 330; Climate risk premia; Transition risk; Physical risk; Text analysis